The Pharmacokinetics of LMW Dermatan Sulphate: Long-Term Persistence of Intact Material - Dawes, Joan (Thrombosis and Haemostasis, 1993)
An iodinated derivative of the low molecular weight dermatan sulphate Desmin 370 was administered to rats by intravenous, subcutaneous and intramuscular routes in conjunction with unlabelled Desmin 370. Following intravenous injection radiolabel was cleared from the plasma according to a tri-exponential function with elimination half-lives of 45 min and 13 h; there was a high concentration in tissues, particularly the kidney, compared with plasma. The apparent bioavailability following s. c. injection was 52-65%, but 84-100% after i. m. administration. Undegraded as well as desulphated molecules were identified in plasma, and intact 125I-Desmin 370 comprised > 85% of the radiolabel in urine 48 h post-injection. Thus intact Desmin 370 persists for a long period after a single injection. The pharmacological significance of these findings, however, remainsto be determined.